An adverse outcome pathway-based approach to assess steatotic mixture effects of hepatotoxic pesticides in vitro. (May 2020) - Lichtenstein, Dajana; Luckert, Claudia; Alarcan, Jimmy; de Sousa, Georges; Gioutlakis, Michail; Katsanou, Efrosini S.; Konstantinidou, Parthena; Machera, Kyriaki; Milani, Emanuela S.; Peijnenburg, Ad; Rahmani, Roger; Rijkers, Deborah; et al.
Abstract: Exposure to complex chemical mixtures requires a tiered strategy for efficient mixture risk assessment. As a part of the EuroMix project we developed an adverse outcome pathway (AOP)-based assay toolbox to investigate the combined effects of the liver steatosis-inducing compounds imazalil, thiacloprid, and clothianidin in human HepaRG hepatocarcinoma cells. Compound-specific relative potency factors were determined using a benchmark dose approach. Equipotent mixtures were tested for nuclear receptor activation, gene and protein expression, and triglyceride accumulation, according to the molecular initiating events and key events proposed in the steatosis AOP. All three compounds affected the activity of nuclear receptors, but not key genes/proteins as proposed. Triglyceride accumulation was observed with three different methods. Mixture effects were in agreement with the assumption of dose additivity for all the combinations and endpoints tested. Compound-specific RPFs remained similar over the different endpoints studied downstream the AOP. Therefore, it might be possible to reduce testing to a smaller battery of key tests. The results demonstrate the suitability of our in vitro assay toolbox, integrated within an AOP framework and combined with the RPF approach, for the analysis of steatotic effects of chemical mixtures. However, mRNA results suggest that the steatosis AOP still needs improvement. Highlights: An AOP-wise testing strategy was developed to assess mixture effects of chemicals. Equipotent mixture designs were performed considering relative compound potencies. The magnitude of effects were consistent with the assumption of dose additivity. Compound-specific relative potencies remained similar over the endpoints studied.